Mean platelet volume, platelet count, and neutrophil/lymphocyte ratio in drug-naïve patients with schizophrenia: a cross-sectional study - Cabello-Rangel, Héctor; Basurto-Morales, Marisol; Botello-Aceves, Elizabeth; Pazarán-Galicia, Osiris (Frontiers in Psychiatry, 2023)
Introduction Mean platelet volume (MPV), platelet count, and neutrophil/lymphocyte ratio (NLR) have been proposed to be biomarkers of the chronic inflammatory process in schizophrenia and indicative of increased cardiovascular risk. Objective To describe MPV, total platelet count (PLT), and NLR between healthy controls and patients with schizophrenia to determine the correlation between these parameters and the duration of untreated psychosis (DUP). Methods In a retrospective cross-sectional study, we included 175 patients with schizophrenia who had never received psychiatric treatment, and who had undergone blood biometry and blood chemistry within 24 h of admission. Laboratory studies were determined by the impedance method on Coulter ac-T 5 diff hematological equipment. Results Mean platelet volume levels in patients with schizophrenia were higher than in healthy controls but not statistically significant. The receiver operating characteristic curve for this parameter shows that the optimal cutoff point of agreement was 8.95 fL, with sensitivity and specificity for schizophrenia of 52% and 67%, respectively, and the area under the curve (AUC) was 0.580 (p = 0.079). DUP had no significant correlation with the blood parameters analyzed. Conclusion The results partially support the hypothesis that MPV, platelet count, and NLR is related to schizophrenia, and further research is needed to establish whether there is an underlying chronic inflammatory process.